5 language visual dictionary. (DK Publishing, 2020)
5 Language Visual Dictionary is a user friendly and intuitive reference for adults learning English, French, German, Spanish, or Italian. The only language dictionary of its kind, 5 Language Visual Dictionary makes language learning accessible by using photographs to put everyday words into context. Its thematic organization of 10,000 terms accompanied by more than 1,600 annotated color photographs and illustrations puts the perfect translation at your fingertips. Additional feature panels include abstract nouns and verbs, as well as useful phrases you can use in conversation. Whether you are a student, tourist, or business traveler, 5 Language Visual Dictionary is your comprehensive guide to learning English, French, German, Spanish, or Italian.